Climate risk scenarios of orange rust for the sugarcane-producing regions of Argentina and Brazil - Angelotti, Francislene; Morales, Cristina Del Carmen; Hamada, Emília; Bisonard, Eduardo Matias; Gonçalves, Renata Ribeiro do Valle; Rago, Alejandro Mario (CDRR Editors, 2022)
Risk analysis of climate change on the spatial distribution of sugarcane orange rust (Puccinia kuehnii) is a strategic study for plant protection to minimize future damages. The objective of this work was to evaluate the potential risk of the occurrence of orange rust in Argentina and Brazil under the climate change scenarios. A mapping methodology integrated the data of climate projections and the phytosanitary problem supported by Geographic Information System (GIS). Normal climate (1961-1990) and future climate (2011-2040, 2041-2070, and 2071-2100) from Intergovernmental Panel on Climate Change were considered. The conditions of climatic favorability for the occurrence of the disease were established by means mathematical logic criteria of GIS, based on knowledge of the authors, who incorporated the implicit effects of the interaction of the virulent pathogen, susceptible host, and predisposing environmental characteristics. The favorability for the occurrence of sugarcane orange rust in the main sugarcane producing regions of Argentina and Brazil varied over the months considered of the cultivation cycle. For Argentina, the future climate scenarios predicted a reduction in favorability for the occurrence of sugarcane orange rust from December to February and an increase in April. In Brazil, the climatic favorability decreased from December to March and increased in May.